Studi Pemulihan Citra Polri dengan Metode Analisis Isi Media dalam Teks Dialog Kapolri di Televisi Berita - Dede Suprayitno; Vika Widiastuti (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2023)
Polri has experienced a crisis of public trust due to a number of cases. To recover, Polri distributed information to a number of news TVs. Data collection was carried out through observation and documentation from dialogues by the National Police Chief Gen. Listyo Sigit Prabowo on TvOne, Metro TV and Kompas TV. This research uses William Benoit's image restoration theory which is studied through the media content analysis method and deepened through Jurgen Habermas' critical hermeneutics study. The aim of this research is to find out what steps the Chief of Police takes in restoring the image of the institution. Especially through the construction of messages built through the media. The results of the study show that some of the cases that have surfaced have distanced Polri from its main duties as maintaining public security and order, enforcing the law, and providing protection, protection, and services to the community. The media content revealed in the three televisions shows the commitment of the National Police Chief to resolve the existing cases. The police realised that the Ferdy Sambo case had a big impact on the institution. Therefore, the public needed clarification and the National Police Chief answered the question. From the stages of image restoration, the National Police Chief shows a lot of reducing effectiveness or explanation of the good of the institution, conveys minimal damage and takes a favourable position and corrective action or the organisation takes corrective action to restore status. To ensure that Polri's image is restored, the National Police Chief must endeavour to keep Polri on the right track, enforce the law fairly and indiscriminately, and return to the noble values of the institution.